Ultra long period reversible fiber gratings as a pressure sensor - Ugale, Sunita Pandit; Mishra, Vivekanand; Amphawan, Angela (Springer Berlin Heidelberg, 2013)
We report here for the first time the fabrication and characterization of mechanically induced ultralong period fiber gratings (MULPFG) with period size up to several millimeters. In these gratings the coupling of the fundamental guided core mode takes place with cladding modes of high diffraction orders. The transmission characteristic of grating with different external applied pressure has been experimentally verified.